Rust: Speeding up file I/O - Tsoukalos, Mihalis (Linux format, 2016)
Hopefully, you'll be feeling more comfortable with Rust, which means it's time to deal with a subject that's very important in systems programming and Operating Systems: file I/O. Rust's strict programming rules come in handy when dealing with files because it reduces errors and bugs and allows you to concentrate on what really matters -- which is the algorithm and the operations that you want to perform. First, Linux Format will present some simple examples before continuing with more advanced topics, such as processing text files and memory-mapped file I/O. This tutorial will also cover some important Rust topics, including pointers, pattern matching and the usize and isize types. The approach that Rust takes is actually quite useful because you write your documentation near your code. However, this assumes that you're willing to write documentation for your code. Rust generates local documentation information for all crates that are used by the project.